Plasmodium vivax circumsporozoite genotypes: a limited variation or new subspecies with major biological consequences? - Souza-Neiras, Wanessa C. [UNESP]; Storti-Melo, Luciane M. [UNESP]; Cassiano, Gustavo C. [UNESP]; Couto, Vanja S. C. A.; Couto, Alvaro A. R. A.; Soares, Irene S.; Carvalho, Luzia H.; Cunha, Maristela G.; Povoa, Marinete M.; Herrera, Socrates; Herrera, Myriam A.; Rossit, Andrea R. B.; et al. (Biomed Central Ltd., 2010)
Background: Plasmodium vivax circumsporozoite variants have been identified in several geographical areas. The real implication of the genetic variation in this region of the P. vivax genome has been questioned for a long time. Although previous studies have observed significant association between VK210 and the Duffy blood group, we present here that evidences of this variation are limited to the CSP central portion.Methods: The phylogenetic analyses were accomplished starting from the amplification of conserved domains of 18 SSU RNAr and Cyt B. The antibodies responses against the CSP peptides, MSP-1, AMA-1 and DBP were detected by ELISA, in plasma samples of individuals infected with two P. vivax CS genotypes: VK210 and P. vivax-like.Results: These analyses of the two markers demonstrate high similarity among the P. vivax CS genotypes and surprisingly showed diversity equal to zero between VK210 and P. vivax-like, positioning these CS genotypes in the same clade. A high frequency IgG antibody against the N- and C-terminal regions of the P. vivax CSP was found as compared to the immune response to the R- and V-repetitive regions (p = 0.0005, Fisher's Exact test). This difference was more pronounced when the P. vivax-like variant was present in the infection (p = 0.003, Fisher's Exact test). A high frequency of antibody response against MSP-1 and AMA-1 peptides was observed for all P. vivax CS genotypes in comparison to the same frequency for DBP.Conclusions: This results target that the differences among the P. vivax CS variants are restrict to the central repeated region of the protein, mostly nucleotide variation with important serological consequences.